Comparison of Coding DNA - Pedersen, Christian N. S.; Lyngsø, Rune B.; Hein, Jotun (BRICS Report Series, 1998)
We discuss a model for the evolutionary distance between two coding DNA sequences which specializes to the DNA/protein model proposed in Hein [3]. We discuss the DNA/protein model in details and present a quadratic time algorithm that computes an optimal alignment of two coding DNA sequences in the model under the assumption of affine gap cost. The algorithm solves a conjecture in [3] and we believe that the constant factor of the running time is sufficiently small to make the algorithm feasible in practice.